CHILDFREE MENURUT PANDANGAN BAHTSUL MASAIL NU DAN MAJELIS TARJIH MUHAMMADIYAH - Asfiyah, Siti; Fikri, Sariatul (USRAH: Jurnal Hukum Keluarga Islam, 2025)
Childfree is a social phenomenon that is currently an interesting topic of discussion. This deserves attention from Islamic law. In the context of Islam in Indonesia, there are several important institutions that provide religious views on various contemporary issues. These institutions include the Bahtsul Masail Nahdlatul Ulama Institute (LBM-NU), and the Muhammadiyah Tarjih Council. This study aims to explore the legal views of the Bahtsul Masail NU Institute and the Muhammadiyah Tarjih Council regarding childfree. This study is a type of library research with a qualitative descriptive approach. The results of the study state that LBM-NU has issued four fatwas regarding refusing to have children. Meanwhile, the Muhammadiyah Tarjih and Tajdid Council in conducting ijtihad uses three approaches, namely Bayani, Burhani and Irfani. Keywords: Childfree, LBM-NU and Muhammadiyah Tarjih Council